Preparation method of urushiol nano-micelle mediated super-viscous and tough hydrogel electrolyte and product of urushiol nano-micelle mediated super-viscous and tough hydrogel electrolyte
By introducing polymer chains with catechol groups into the hydrogel network and self-assembly the unsaturated linear hydrocarbon structure of uugeol to form uugeol nano micelles, the performance fluctuations and failure problems caused by insufficient interface adhesion in flexible batteries are solved, and a hydrogel electrolyte with high adhesion and mechanical stability is achieved.
Patent Information
- Application Number
- CN202411622213.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-03-25
AI Technical Summary
Due to the lack of reliable interface bonding force of existing hydrogel electrolytes, the interfacial collapse of the flexible battery caused slippage and interlayer separation between the internal gel electrolyte and the electrode during the complex mechanical deformation process, causing fluctuations, attenuation, and even failure of the battery performance.
The polymer chains with catechol groups are coupled into the hydrogel network and self-assembled using the natural unsaturated linear hydrocarbon structure of uuol to form a uuol nanomicrobes, which are copolymerized and cross-linked with other monomers as crosslinking points to form a super viscous and tough hydrogel electrolyte.
The high adhesion, mechanical stability and long-term stability of hydrogel electrolytes are achieved, and the failure problems caused by interfacial slip and separation of batteries are avoided under variable mechanical loads.
Smart Images

Figure CN119684535A_ABST
Abstract
Description
[Technical field]
[0001] The invention relates to the technical field of biomass functional materials, and in particular to a preparation method of an ultra-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles and a product thereof. [Background technology]
[0002] Flexible zinc-ion batteries based on hydrogel electrolytes have become a new generation of flexible batteries with great commercial prospects due to their high safety, low cost, high energy output, abundant zinc reserves and environmental friendliness. Flexible batteries will inevitably be impacted by complex and variable mechanical loads such as bending, stretching, folding and twisting during application. During operation, the hydrogel electrolyte must always be tightly bonded to the electrode surface to ensure smooth ion transmission channels. However, due to the lack of reliable interfacial adhesion in existing hydrogel materials, flexible batteries suffer from interfacial collapse problems such as slippage and interlayer separation between the internal gel electrolyte and the electrode during complex mechanical deformation, causing battery performance fluctuations, attenuation, and even failure. Therefore, there is an urgent need to construct hydrogel electrolytes with strong interfacial adhesion and high mechanical stability in the field of flexible energy storage. To achieve strong adhesion between the hydrogel electrolyte and the electrode surface, it is required that the hydrogel electrolyte structure has specific functional groups that can form strong interaction forces with the electrode material. Marine mussels rely on their byssus to secrete dopamine-rich sticky substances to achieve tight adhesion to various surfaces. Studies have shown that the catechol group of dopamine can interact with a variety of surfaces by forming covalent bonds or non-covalent bonds to achieve strong interfacial adhesion.
[0003] Inspired by this, coupling a polymer chain with a catechol group into a hydrogel network to construct a hydrogel material with high adhesion has been confirmed by many researchers as an effective method. For example, CN 115975319B discloses a highly self-adhesive polyvinyl alcohol-based hydrogel and a preparation and molding method thereof, by introducing a carboxyl group (CPVA) on the polyvinyl alcohol molecular chain, and using a hybrid of highly self-adhesive polydopamine (PDA) with a mussel adhesion protein structure and graphene oxide (GO) as a crosslinker, and using the covalent / non-covalent interaction between the GO-PDA hybrid crosslinker and the CPVA molecules to form a multiple crosslinked network structure, thereby obtaining a highly self-adhesive polyvinyl alcohol-based hydrogel, which is endowed with excellent adhesion to a variety of material substrates such as human skin. However, the construction of such adhesive hydrogels usually requires complex chemical modifications such as oxidative pre-polymerization of dopamine, functional modification (such as introducing double bonds) or grafting it onto polymer molecular chains. The process usually involves a large amount of organic solvents, and the steps are cumbersome, time-consuming, and have low yields. In addition, the key functional unit dopamine is extremely expensive and difficult to obtain, resulting in dopamine-based adhesive hydrogel electrolytes not being widely used in the field of flexible batteries.
[0004] Raw lacquer is a high-quality natural product resource with Chinese characteristics. It is a natural resin with good adhesion, excellent mechanical properties, natural renewability and environmental friendliness. Urushiol is the main compound of raw lacquer. It has an ortho-bisphenol hydroxyl group (catechol structure) with a dopamine-like structure, and the R side chain on the benzene ring is a C15-C17 straight-chain hydrocarbon structure (unsaturation: 0-3). It is a high-quality natural resource for constructing super-adhesive hydrogel electrolytes.
[0005]
[0006] The applicant has found that compared with dopamine, the natural unsaturated straight-chain hydrocarbon structure unique to urushiol can directly participate in free radical polymerization reactions, providing great convenience for the catechol group to be anchored into the polymer molecular chain, avoiding the cumbersome chemical modification for introducing dopamine into the polymer molecular chain, and is an ideal substitute for dopamine. At the same time, the price of urushiol (~400 yuan / kg) is only 1 / 20 of that of dopamine. When urushiol is introduced into the hydrogel network structure, the catechol group in the urushiol molecular structure is easy to form a stable interface bond with the electrode material through covalent or non-covalent bonds, providing strong interface adhesion for the hydrogel electrolyte, and preventing the gel electrolyte-electrode adhesion interface from being destroyed due to the deformation of the flexible battery under stress.
[0007] Based on the unsaturated long straight-chain hydrocarbon structure of urushiol, surfactant micelles are used as nanocontainers to self-assemble urushiol nanomicelle aggregates, which are then crosslinked with other monomers to form super-viscous and tough hydrogel electrolytes. The catechol adhesive groups and long-chain hydrocarbon hydrophobic association micro-region energy dissipation structure in urushiol nanomicelles can not only achieve the viscosity and toughness of hydrogel electrolytes, and solve the battery failure problem of electrolyte / electrode interface collapse caused by weak interfacial adhesion and low cohesion in current hydrogel electrolytes, but also adjust the balance between cohesion and adhesion of the system by adjusting the proportion of functional components, so as to achieve long-term stability of the electrochemical performance of flexible zinc-ion batteries under variable mechanical loads, and provide a theoretical and technical basis for the development of new bio-based high-performance flexible zinc-ion battery hydrogel electrolytes that have both mussel-like superadhesion and strong creep resistance. This method is simple to operate, and the raw materials used are from natural products, which is green and environmentally friendly, and highly safe. It can provide a new technical guidance for the preparation of flexible zinc-ion battery hydrogel electrolytes with excellent performance. [Summary of the invention]
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a super-viscous and tough hydrogel electrolyte mediated by lacquer phenol nano-micelles and its product. The process is simple, green and environmentally friendly, with abundant raw material resources and high safety. A high-performance flexible zinc ion battery hydrogel electrolyte with excellent mechanical stability, durability and electrochemical properties, as well as mussel-like super-adhesion and strong anti-creep cohesive force is prepared.
[0009] The present invention is achieved in that:
[0010] A method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles, the method comprising the following steps:
[0011] (1) adding natural urushiol to a surfactant aqueous solution at room temperature, and self-assembling under ultrasonic stirring to form an urushiol nano-micelle aqueous solution; wherein the surfactant solubility is 5-30%, and the mass percentage content of urushiol is 1-40%;
[0012] (2) adding zinc salt to the aqueous solution of urushiol nano-micelles in step (1), stirring and dissolving, adding a water-soluble monomer containing a double bond, a cross-linking agent and a photoinitiator, continuing to stir until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution; wherein the solubility of the zinc salt is 0.5-3 mol / L, the content of the water-soluble monomer containing a double bond is 2-100 times that of the urushiol, the content of the cross-linking agent is 1‰ to 5‰ of the water-soluble monomer containing a double bond, and the content of the free radical photoinitiator is 1‰ to 5‰ of the water-soluble monomer containing a double bond;
[0013] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold, and ultraviolet light of 365 nm was used to induce copolymerization of urushiol nano-micelles and monomers at room temperature to obtain an ultraviolet-induced hydrogel electrolyte.
[0014] Furthermore, the surfactant in step (1) is a mixture of one or more of sodium lignin sulfonate, calcium lignin sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, dioctyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate and rosin-based surfactant; and the ultrasonic power is 50W.
[0015] Furthermore, the rosin-based surfactant is a rosin-based sulfate surfactant R-6-SO4Na, a rosin-based glucose surfactant R-6-Glu, or a rosin-based sulfobetaine amphoteric surfactant.
[0016] Furthermore, the zinc salt in step (2) is one or a mixture of ZnSO4, Zn(NO3)2, ZnCl2, Zn(CH3COO)2, ZnF2, Zn(ClO4)2 and Zn(CF3SO3)2.
[0017] Furthermore, the double bond-containing polymerizable water-soluble monomer in step (2) is one or a mixture of N-isopropylacrylamide, acrylic acid, acrylamide and methoxyethyl acrylate.
[0018] Furthermore, the cross-linking agent in step (2) is N,N-methylenebisacrylamide or polyethylene glycol diacrylate.
[0019] Further, the free radical photoinitiator in step (2) is 2-hydroxy-2-methyl-1-phenylpropanone, 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and (2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone.
[0020] Furthermore, in step (3), the luminescence initiation time is 5-15 minutes.
[0021] Furthermore, a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles is provided, and the super-viscous and tough hydrogel electrolyte is prepared based on the preparation method of the super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles.
[0022] The present invention has the following advantages:
[0023] The present invention utilizes the unsaturated long straight-chain hydrocarbon structure of urushiol, uses surfactant micelles as nano-containers, obtains urushiol nano-micelle aggregates by self-assembly, and uses them as crosslinking points to form super-viscous and tough hydrogel electrolytes by photoinitiated copolymerization and crosslinking with other monomers in one step. The catechol groups of the urushiol nano-micelles in this novel hydrogel electrolyte provide it with strong interfacial adhesion, ensuring the stability of the bonding interface between the gel electrolyte and the electrode material in the flexible battery under complex bending working conditions. In addition, the physical effects of the internal hydrophobic long straight-chain hydrocarbons of the urushiol nano-micelles, such as sliding friction, disentanglement and micelle deformation, provide additional energy dissipation for the hydrogel electrolyte, enhance the cohesion of the hydrogel electrolyte, and effectively solve the brittleness problem of the covalent bond network in the traditional gel electrolyte. By adjusting the ratio of the urushiol nano-micelles to other components, the balance between the cohesion and adhesion in the hydrogel electrolyte is regulated, thereby further enhancing the mechanical stability and durability of the hydrogel, optimizing its electrochemical properties, and preparing a high-performance flexible zinc ion battery hydrogel electrolyte that has both mussel-like superadhesion and strong anti-creep cohesion. The invention has simple process, is green and environmentally friendly, has abundant raw material resources and high safety, and provides a new type of hydrogel electrolyte with low carbon, environmental friendliness and excellent performance for flexible zinc ion batteries.
Brief Description of the Drawings
[0024] The present invention will be further described below in conjunction with embodiments with reference to the accompanying drawings.
[0025] Figure 1 The present invention provides a technical roadmap for the ultra-viscous and tough hydrogel electrolyte mediated by lacquer phenol nano-micelles.
[0026] Figure 2 1 is a particle size distribution diagram of different micelles in Example 1 of the present invention; wherein, (a) is a particle size distribution test result, and (b) is a particle size distribution statistical diagram.
[0027] Figure 3 FTIR spectra of the hydrogel electrolyte synthesized in Example 1 of the present invention, the hydrogel electrolyte synthesized in Comparative Example 1, and urushiol.
[0028] Figure 4 Schematic diagram of the effect of different urushiol contents on the mechanical properties of the hydrogel electrolyte in the embodiments of the present invention.
[0029] Figure 5 It is a schematic diagram of the effects of different urushiol contents and different substrates on the mechanical properties of the hydrogel electrolyte in the embodiments of the present invention.
[0030] Figure 6 Schematic diagram of the electrochemical performance of the hydrogel electrolyte prepared in Example 4 of the present invention; wherein (a) is an EIS curve, and (b) is an LSV curve.
[0031] Figure 7 This is a constant current charge and discharge test diagram of a Zn|hydrogel electrolyte|Zn symmetric battery in an embodiment of the present invention.
[0032] Figure 8 Schematic diagram of the performance test of the flexible zinc ion battery based on the hydrogel electrolyte of Example 2 of the present invention; wherein: (a) rate performance test; (b) charge and discharge curve; (c) cycle stability test.
[0033] Fig. 9 Schematic diagram of the flexible zinc ion battery based on lacquer phenol nanomicelle hydrogel electrolyte of Example 5 of the present invention supplying power to an LED lamp under different conditions; wherein, (a) normal conditions; (b) 135° bending angle; (c) hammering by external force; and (d) shear tearing.
[0034] Fig.10 This is a schematic diagram of the anti-bending electrochemical performance test of the flexible zinc ion battery based on the lacquer phenol nano-micelle hydrogel electrolyte of Example 5 of the present invention; wherein, (a) the cycle stability at different bending angles; and (b) the charge and discharge curves at different bending angles. [Specific implementation method]
[0035] See also Figure 1 The present invention relates to a method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles, and the method comprises the following steps:
[0036] (1) adding natural urushiol to a surfactant aqueous solution at room temperature, and self-assembling under ultrasonic stirring to form an urushiol nano-micelle aqueous solution; wherein the surfactant solubility is 5-30%, and the mass percentage content of urushiol is 1-40%;
[0037] (2) adding zinc salt to the aqueous solution of urushiol nano-micelles in step (1), stirring and dissolving, adding a water-soluble monomer containing a double bond, a cross-linking agent and a photoinitiator, continuing to stir until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution; wherein the solubility of the zinc salt is 0.5-3 mol / L, the content of the water-soluble monomer containing a double bond is 2-100 times that of the urushiol, the content of the cross-linking agent is 1‰ to 5‰ of the water-soluble monomer containing a double bond, and the content of the free radical photoinitiator is 1‰ to 5‰ of the water-soluble monomer containing a double bond;
[0038] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold, and ultraviolet light of 365 nm was used to induce copolymerization of urushiol nano-micelles and monomers at room temperature to obtain an ultraviolet-induced hydrogel electrolyte.
[0039] And the product prepared by the preparation method of the above-mentioned lacquer phenol nano-micelle-mediated super-viscous and tough hydrogel electrolyte.
[0040] The following will be combined with the attached Figure 2-10 The technical scheme of the present invention is clearly and completely described in detail with specific embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be purchased commercially.
[0041] Example 1
[0042] (1) At room temperature, 10 g of sodium dodecyl sulfate was dissolved in 90 mL of deionized water, and then 5 g of natural urushiol was added. Ultrasonic stirring (power of 50 W) was performed for 10 min to self-assemble into an aqueous solution of urushiol nanomicelles.
[0043] (2) 14 g ZnCl2 was added to the aqueous solution of urushiol nanomicelles in step (1), and after stirring to dissolve, 25 g acrylic acid monomer, 0.2 g polyethylene glycol diacrylate and 0.06 g photoinitiator (1173) were added, and stirring was continued until completely dissolved, and then vacuum degassing was performed to obtain a uniform mixed solution.
[0044] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (length 50 mm; width 50 mm; thickness 1 mm). At room temperature, the urushiol nano-micelles were copolymerized with acrylamide monomers under the initiation of ultraviolet light at 365 nm (15 min) to obtain an ultraviolet-induced hydrogel electrolyte.
[0045] Example 2
[0046] (1) At room temperature, 15 g of sodium dodecyl sulfate was dissolved in 85 mL of deionized water, and then 8 g of natural urushiol was added and stirred by ultrasound (power of 50 W) for 10 min to self-assemble into an aqueous solution of urushiol nanomicelles.
[0047] (2) 15 g of ZnSO4 was added to the aqueous solution of urushiol nanomicelles in step (1), and after stirring to dissolve, 20 g of acrylamide monomer, 0.2 g of N,N-methylenebisacrylamide and 0.02 g of photoinitiator (IHT-PI 910) were added, and stirring was continued until completely dissolved, and then vacuum degassing was performed to obtain a uniform mixed solution.
[0048] (3) Preparation of ultraviolet-light-induced micelle copolymerization mediated by lacquer phenol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (length 50 mm; width 50 mm; thickness 1 mm). At room temperature, the lacquer phenol nano-micelles were copolymerized with acrylic acid monomers under the initiation of ultraviolet light at 365 nm (10 min) to obtain an ultraviolet-light-induced hydrogel electrolyte.
[0049] Example 3
[0050] (1) At room temperature, 12 g of rosin-based sulfate surfactant R-6-SO4Na was dissolved in 88 mL of deionized water, and then 10 g of natural urushiol was added. Ultrasonic stirring (power of 50 W) was performed for 10 min to self-assemble into an aqueous solution of urushiol nanomicelles.
[0051] (2) Add 14 g Zn(CF3SO3)2 to the aqueous solution of lacquer phenol nanomicelles in step (1), stir to dissolve, then add 25 g acrylamide monomer, 0.4 g N,N-methylenebisacrylamide and 0.02 g photoinitiator (659), continue stirring until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution.
[0052] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (length 50 mm; width 50 mm; thickness 1 mm). At room temperature, the urushiol nano-micelles were copolymerized with acrylamide monomers under the initiation of ultraviolet light at 365 nm (15 min) to obtain an ultraviolet-induced hydrogel electrolyte.
[0053] Example 4
[0054] (1) At room temperature, 10 g of sodium lignin sulfonate surfactant was dissolved in 90 mL of deionized water, and then 15 g of natural urushiol was added and stirred by ultrasound (power of 50 W) for 10 min to self-assemble into an aqueous solution of urushiol nanomicelles.
[0055] (2) Add 15 g Zn(ClO4)2 to the aqueous solution of lacquer phenol nanomicelles in step (1), stir to dissolve, then add 50 g N-isopropylacrylamide monomer, 0.5 g polyethylene glycol diacrylate and 0.03 g photoinitiator (907), continue stirring until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution.
[0056] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (length 50 mm; width 50 mm; thickness 1 mm). At room temperature, the urushiol nano-micelles were copolymerized with acrylamide monomers under the initiation of ultraviolet light at 365 nm (15 min) to obtain an ultraviolet-induced hydrogel electrolyte.
[0057] Example 5
[0058] (1) At room temperature, 15 g of sodium dioctyl succinate sulfonate surfactant was dissolved in 85 mL of deionized water, and then 16 g of natural urushiol was added and ultrasonically stirred (power of 50 W) for 10 min to self-assemble into an aqueous solution of urushiol nanomicelles.
[0059] (2) Add 14 g Zn(CH3COO)2 to the aqueous solution of lacquer phenol nanomicelles in step (1), stir to dissolve, then add 100 g acrylic acid monomer, 0.4 g N,N-methylenebisacrylamide and 0.02 g photoinitiator (659), continue stirring until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution.
[0060] (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (length 50 mm; width 50 mm; thickness 1 mm). At room temperature, the urushiol nano-micelles were copolymerized with acrylamide monomers under the initiation of ultraviolet light at 365 nm (15 min) to obtain an ultraviolet-induced hydrogel electrolyte.
[0061] Comparative Example 1
[0062] (1) At room temperature, 10 g of sodium dodecyl sulfate was dissolved in 90 mL of deionized water and stirred by ultrasound (power of 50 W) for 10 min to obtain an aqueous solution of sodium dodecyl sulfate.
[0063] (2) 14 g ZnCl2 was added to the sodium dodecyl sulfonate aqueous solution in step (1), and after stirring to dissolve, 20 g acrylamide monomer, 0.2 g N,N-methylenebisacrylamide and 0.02 g photoinitiator (IHT-PI 910) were added, and stirring was continued until completely dissolved, and then vacuum degassing was performed to obtain a uniform mixed solution.
[0064] (3) Preparation of polyacrylamide hydrogel electrolyte by one-step ultraviolet light-induced micellar copolymerization: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold (50 mm long, 50 mm wide, and 1 mm thick), and acrylamide monomer was copolymerized under 365 nm ultraviolet light (15 min) at room temperature to obtain a polyacrylamide hydrogel electrolyte.
[0065] Application Example 1
[0066] Assembly of flexible battery: This embodiment provides a flexible battery, in which the super-viscous and tough lacquer phenol nano-micelle hydrogel electrolyte prepared in Examples 1-5 is directly used as an aqueous zinc ion battery electrolyte without an additional separator, and metallic zinc is used as the anode. Manganese dioxide / carbon nanotubes, superconducting carbon black and polyvinylidene fluoride are uniformly mixed and ground into a slurry in a mass ratio of 7:2:1 in N-methylpyrrolidone, and coated on a titanium foil as a current collector. After drying at 90°C, an electrode sheet is punched out to prepare a cathode, and a flexible battery is assembled with a negative electrode shell, a zinc sheet, a gel electrolyte and a cathode on a laboratory bench exposed to air.
[0067] Results and Analysis:
[0068] 1. Particle size analysis
[0069] The micelle particle size of Example 1 was tested using a laser particle size analyzer. Surfactants generally exist in the form of spherical micelles in the solution, such as Figure 2 As shown, the micelle particle size of pure sodium dodecyl sulfate is about 3nm. With the addition of zinc chloride, the micelle size increases to about 6nm. After the introduction of urushiol, the micelle particle size further increases to 18nm, indicating that urushiol and sodium dodecyl sulfate self-assemble to form new urushiol nano-micelles, thereby promoting micelle growth. The increase in micelle particle size is beneficial to the subsequent micelle copolymerization, thereby promoting the improvement of the cohesion of the hydrogel electrolyte. Larger micelles can more effectively encapsulate hydrophobic urushiol monomers, thereby forming more physical cross-linking points in the gel network. These physical cross-linking points are formed by the interweaving of straight-chain hydrocarbons on the side chains of urushiol units. They form dense hydrophobic association micro-regions in the hydrophobic core of the gel. These cross-linking points increase the fracture stress, elastic modulus and toughness (i.e., cohesion) of the gel electrolyte.
[0070] 2. Characterization of chemical structure
[0071] The chemical structure of the urushiol nano-micelle hydrogel electrolysis of Example 1 was characterized by Fourier transform infrared spectroscopy. Figure 3 As shown, urushiol is at 3380.6 cm -1 (-OH stretching vibration), 3012.8cm -1 (=CH stretching vibration), 982.6cm -1 and 945.3cm -1 The hydrogel electrolyte in Comparative Example 1 has an obvious characteristic peak at 1660.9 cm -1 (C=O stretching) and 1430.6 cm -1 The absorption peak of (NH bending) is the characteristic peak of polyacrylamide. In the infrared spectrum of hydrogel electrolysis of Example 1, 3012.8 cm -1 、982.6cm -1 and 945.3cm -1 disappeared, indicating that urushiol and acrylamide successfully copolymerized. In addition, compared with Comparative Example 1, the hydrogel of Example 1 -1 The -OH stretching vibration absorption peak significantly red-shifted to 3240.1 cm -1 This is mainly due to the strong hydrogen bonding between the phenolic hydroxyl groups on the benzene ring of urushiol and the polyacrylamide molecular chain.
[0072] 3. Investigate the effect of urushiol content on the electromechanical properties of hydrogels
[0073] Taking the gel electrolyte prepared in Example 2 as an example, the effects of 0%, 10%, 20%, 30%, 40%, and 50% of urushiol added (accounting for the amount of acrylamide) on the mechanical properties of urushiol nano-micelle hydrogel electrolyte were investigated. Figure 4 As shown in the figure, within a certain range, as the content of urushiol increases, the toughness and strength of the gel electrolyte are significantly improved. When the content of urushiol is 0%, the strain of the hydrogel electrolyte is only 269.75%, the fracture stress is 7.7kPa, and the elastic modulus is 2.9kPa; when 10% of urushiol is added, the strain of the hydrogel electrolyte rapidly increases to 1398%, and the fracture stress increases to 36.5kPa, and its strain and stress have doubled. When the addition amount of urushiol is 40%, the strain of the hydrogel electrolyte is 2902%, the fracture stress is 217.3kPa, and the elastic modulus is 7.5kPa, which are 10 times, 28 times, and 2.6 times of those when the content of urushiol is 10%, respectively. This is mainly because with the increase of the content of urushiol, there are more polymerizable active sites inside the nanomicelles, so that the gel electrolyte forms a more compact network structure during the micelle copolymerization process, thereby improving the cohesion of the gel.
[0074] 4. Investigate the effect of urushiol content on the electrolytic adhesion properties of nanomicelle hydrogel
[0075] Taking the gel electrolyte prepared in Example 3 as an example, the effects of 0%, 10%, 20%, 30%, 40%, and 50% urushiol addition (accounting for the amount of acrylamide) on the adhesion of the hydrogel electrolyte were investigated. The adhesion strength of the hydrogel of Example 3 to different substrates was quantitatively analyzed by tensile shear experiments. The catechol group of urushiol can form a complex with zinc ions to enhance the adhesion of the hydrogel electrolyte to the zinc surface. This complexation is crucial to improving the adhesion strength of the hydrogel electrolyte on the flexible zinc electrode. Figure 5 As shown in Fig. 1, the bonding strength of the hydrogel electrolyte of Example 3 to the zinc sheet increases significantly with the increase of the urushiol content. This is mainly due to the fact that the higher the urushiol content, the higher the density of catechol groups per unit area on the gel surface, thereby enhancing the interaction between the gel surface and the zinc surface. Figure 5 As shown in Figure 2, when the amount of lacquer phenol added to the hydrogel of Example 3 is fixed at 40%, the gel electrolyte exhibits good adhesion to different substrates, including hydrophilic materials such as aluminum sheet (adhesion strength is 20.4KPa), zinc sheet (28.2KPa) and wood (31.8KPa), as well as hydrophobic materials such as glass (9.3KPa) and polytetrafluoroethylene (5.3KPa). Among them, the hydrogel electrolyte has the strongest adhesion to wood, which is mainly due to the synergistic effect of hydrogen bonds, hydrophobic effects and π-π effects between the hydrogel and the hydroxyl, carboxyl and aromatic groups on the surface of the wood. In addition, compared with other substrates, the porous structure of the wood surface may also play a certain positive role in the adhesion of the hydrogel. The good adhesion of the hydrogel electrolyte of Example 3 to zinc sheet (28.2KPa) and aluminum sheet (20.4KPa) can be attributed to the synergistic effect between metal coordination bonds and hydrogen bonds, while hydrogen bonds and hydrophobic effects are the main physical interactions for the adhesion of the gel electrolyte to glass (9.3KPa) and polytetrafluoroethylene (5.3KPa).
[0076] 5. AC impedance test of urushiol nanomicelle hydrogel electrolyte
[0077] like Figure 6 As shown in a, the AC impedance test of the urushiol nano-micelle hydrogel electrolyte of Example 4 was performed. The prepared hydrogel electrolyte has a thickness of 2.36 mm, a resistance R of 8.03 Ω, and an area A of 2 cm 2 , through ionic conductivity σ = L / (R×A), the ionic conductivity σ is 1.469×10 -2 S / cm. This electrolyte has a high ionic conductivity and can meet the requirements of zinc ion battery electrolytes. Figure 6As shown in Figure b, the electrochemical stability window of the hydrogel electrolyte of Example 4 was tested. The decomposition voltage of the electrolyte is 2.36V, which is higher than the voltage range of Mn-based zinc ion batteries (<2V), so the hydrogel electrolyte can meet the needs of manganese-based zinc ion batteries.
[0078] 6. Assemble symmetrical batteries for constant current charge and discharge test
[0079] Taking the hydrogel electrolyte of Example 2 as an example, a Zn|hydrogel electrolyte|Zn symmetric battery was assembled, and then a constant current charge and discharge test was performed. Before the hydrogel electrolyte was assembled into a flexible zinc ion battery, a Zn|Zn symmetric battery was assembled with it, and then the reversibility and stability of the zinc electrode in the hydrogel electrolyte of Example 2 were tested by constant current charge and discharge experiments. The Zn|Zn symmetric battery assembled with the hydrogel electrolyte of Example 2, as shown in FIG. Figure 8 As shown, the constant current density is 1mA / cm 2 During the 2000h of the constant current charge and discharge experiment, the voltage was stable, and there was no short circuit or rapid increase in overvoltage, which indicates that the interface stability between the zinc electrode and the electrolyte is relatively good in the constant current charge and discharge test.
[0080] 7. Electrical performance test of flexible zinc-ion battery with hydrogel electrolyte
[0081] Figure 8 a is the rate performance test of the hydrogel electrolyte-based flexible zinc ion battery in Example 2. Under the current charge and discharge conditions of 0.5A, the discharge specific capacity of the flexible zinc ion battery can reach 214.5mAh / g. Even under the high current charge and discharge conditions of 3A, the discharge specific capacity is still 146.2mAh / g. When restored to 0.5A, the discharge specific capacity can be restored to 212.9mAh / g. This shows that after different current charge and discharge conditions, the battery has excellent capacity recovery performance and good cycle stability; Figure 8 b is the charge and discharge curve at different rates. In order to more intuitively observe the cycle performance of the flexible zinc ion battery based on the hydrogel electrolyte of Example 2, a cycle test was performed on it. Figure 8 As shown in Figure c, the battery exhibits excellent electrochemical cycle stability. At 1A / g, the first cycle discharge capacity of the flexible zinc-ion battery is 195.5mAh / g. After 1000 cycles, the discharge capacity can still be maintained at 172.8mAh / g, and the capacity retention rate can reach 88.38%.
[0082] 8. Application of flexible zinc-ion batteries in flexible energy storage devices
[0083] Fig. 9The practicality of flexible zinc ion batteries based on lacquer phenol nanomicelle hydrogel electrolyte in flexible energy storage devices is demonstrated. Fig. 9 aThe actual demonstration of connecting two flexible zinc-ion batteries in series to power multiple light-emitting diodes. When two flexible zinc-ion batteries are connected in series to form a closed circuit, they can successfully power multiple LED lights and emit light for a long time. In order to examine the energy supply of flexible zinc-ion batteries under special conditions (such as bending, deformation, extrusion, etc.), we tested the actual power supply of the battery under a maximum bending of 135°, high pressure, and a certain degree of tearing. The results are as follows Fig. 9 As shown in bd, two flexible zinc-ion batteries can still make multiple light-emitting diodes emit light normally after being bent, folded, hammered, and single-torn and bonded. For further quantitative evaluation, such as Fig.10 As shown in Figure 2, the electrochemical stability of the flexible zinc-ion battery was tested at different bending degrees (0°, 45°, 90°, and 135°). Fig.10 As shown in a, even if the flexible zinc-ion battery is bent into different states, its cycle stability remains stable. After continuous bending, the discharge capacity does not decrease significantly and remains stable at 183.5 mAh / g. Fig.10 As shown in b, under different bending conditions, the discharge curves of the flexible zinc-ion battery almost overlap.
[0084] The above results show that the assembled flexible zinc-ion battery has excellent electrochemical stability under different curvatures. The above results show that the enhanced adhesion of urushiol nanomicelles is crucial to improving the flexibility and wearability of batteries, long-term reliability and overall performance, especially in the development of high-performance, high-stability and high-safety flexible batteries and wearable electronic devices. The catechol groups on the surface of urushiol nanomicelles enhance the adhesion between the hydrogel electrolyte and the flexible zinc electrode surface, improve the mechanical properties and conductivity, ensure stable contact between the electrode and the electrolyte, reduce interfacial slip and stratification, and thus improve the battery's cycle stability, electrochemical performance and safety.
[0085] In summary, the present invention utilizes the unique chemical structure and excellent properties of natural urushiol, uses surfactant micelles as nanocontainers, self-assembles to form urushiol nanomicelles, and prepares a high-performance urushiol nanomicelle hydrogel electrolyte for flexible zinc ion batteries through photoinitiated micelle copolymerization technology. This new hydrogel electrolyte achieves viscosity and toughness of the hydrogel electrolyte through catechol adhesive groups and long-chain hydrocarbon hydrophobic association micro-region energy dissipation structures in the nanomicelles, solves the battery failure problem of electrolyte / electrode interface collapse caused by weak interfacial adhesion and low cohesion of traditional hydrogel electrolytes, and achieves long-term stability of electrochemical performance of flexible zinc ion batteries under variable mechanical loads. In addition, the technology uses natural urushiol and green chemical processes, which not only reduces production costs, but also ensures the environmental sustainability of the product, and also meets the current high standards for environmental sustainability, with high cost-effectiveness. The technology provides technical support for the design and development of hydrogel electrolytes with excellent performance.
[0086] Although the specific implementation modes of the present invention are described above, those skilled in the art should understand that the specific implementation modes described are only illustrative and are not intended to limit the scope of the present invention. Equivalent modifications and changes made by those skilled in the art in accordance with the spirit of the present invention should be included in the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles, characterized in that: The method steps are as follows: (1) adding natural urushiol to a surfactant aqueous solution at room temperature, and self-assembling under ultrasonic stirring to form an urushiol nano-micelle aqueous solution; wherein the surfactant solubility is 5-30%, and the mass percentage content of urushiol is 1-40%; (2) adding zinc salt to the aqueous solution of urushiol nano-micelles in step (1), stirring and dissolving, adding a water-soluble monomer containing a double bond, a cross-linking agent and a photoinitiator, continuing to stir until completely dissolved, and then vacuum degassing to obtain a uniform mixed solution; wherein the solubility of the zinc salt is 0.5-3 mol / L, the content of the water-soluble monomer containing a double bond is 2-100 times that of the urushiol, the content of the cross-linking agent is 1‰ to 5‰ of the water-soluble monomer containing a double bond, and the content of the free radical photoinitiator is 1‰ to 5‰ of the water-soluble monomer containing a double bond; (3) Preparation of ultraviolet-induced micelle copolymerization mediated by urushiol nano-micelles: The homogeneous mixed solution prepared in step (2) was introduced into a sealed transparent glass mold, and ultraviolet light of 365 nm was used to induce copolymerization of urushiol nano-micelles and monomers at room temperature to obtain an ultraviolet-induced hydrogel electrolyte.
2. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The surfactant in step (1) is a mixture of one or more of sodium lignin sulfonate, calcium lignin sulfonate, sodium dodecyl sulfate, sodium dodecyl sulfonate, dioctyl sodium sulfosuccinate, sodium dodecylbenzene sulfonate and a rosin-based surfactant; and the ultrasonic power is 50W.
3. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 2, characterized in that: The rosin-based surfactant is a rosin-based sulfate surfactant R-6-SO4Na, a rosin-based glucose surfactant R-6-Glu, and a rosin-based sulfobetaine amphoteric surfactant.
4. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The zinc salt in step (2) is one or a mixture of ZnSO4, Zn(NO3)2, ZnCl2, Zn(CH3COO)2, ZnF2, Zn(ClO4)2 and Zn(CF3SO3)2.
5. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The double bond-containing polymerizable water-soluble monomer in step (2) is one or a mixture of N-isopropylacrylamide, acrylic acid, acrylamide and methoxyethyl acrylate.
6. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The cross-linking agent in step (2) is N,N-methylenebisacrylamide or polyethylene glycol diacrylate.
7. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The free radical photoinitiator in step (2) is 2-hydroxy-2-methyl-1-phenylpropanone, 2-dimethylamino-2-benzyl-1-[4-(4-morpholinyl)phenyl]-1-butanone, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]-1-propanone and (2-methyl-2-(4-morpholinyl)-1-[4-(methylthio)phenyl]-1-propanone.
8. The method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to claim 1, characterized in that: The luminescence initiation time in step (3) is 5-15 minutes.
9. A super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles, characterized in that: The super-viscous and tough hydrogel electrolyte is prepared based on the method for preparing a super-viscous and tough hydrogel electrolyte mediated by urushiol nano-micelles according to any one of claims 1 to 8.